Prognostic significance of Bcl-2 gene protein family polymorphisms in patients with chronic lymphocytic leukaemia - Joks, Monika; Lewandowski, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2008)
B-cell chronic lymphocytic leukaemia (B-CLL) is the most frequent type of leukaemia in the western hemisphere. It is an incurable disease, and is characterized by expansion of monoclonal malignant lymphoid B cells expressing on the surface CD 19, CD22, CD79b, CD23, CD5, CD20 low, CD5 , k/l (+) low. Leukaemic cells are present in the peripheral blood, bone marrow, and lymphoid tissues. In patients with B-CLL survival and time to progression are highly variable. Failed apoptosis plays an important role in pathogenesis of B-CLL. We present recent data concerning the role of Bcl-2 family proteins in regulation of apoptosis in B-CLL. We focus special attention on the BCL-2, BAX, MCL-1 genes polymorfphisms as potential novel prognostic risk factors in B-CLL patients.